Strategies to Enhance the Competitiveness of MSMEs in the Wali Songo Tourism Area through Fintech and Business Administration for Achieving the SDGs - Setyawati, Amelia; Ibadil Maula, Farij; Sulistyowati, Raya; Sugangga, Rayyan; Wahid, Moehammad Nasri Abdoel; Trisnawati, Novi (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2025)
Phenomenon/Issue: Micro, Small, and Medium Enterprises (MSMEs) operating in the Wali Songo religious tourism area hold strategic potential in driving local economic growth and supporting the achievement of the Sustainable Development Goals (SDGs). Purpose: This study aims to formulate strategies to enhance the competitiveness of MSMEs through the utilization of financial technology (fintech) innovations and the strengthening of business administration as key leverage instruments to support the achievement of the SDGs Novelty: The novelty of this research lies in its integrative approach, which emphasizes the synergy between fintech innovation and practical business administration within the unique local context of religious tourism. It directly links these efforts to SDG indicators, particularly financial inclusion, inclusive economic growth, and poverty reduction. Research Methods: The novelty of this research lies in its integrative approach, which emphasizes the synergy between fintech innovation and practical business administration within the unique local context of religious tourism. It directly links these efforts to SDG indicators, particularly financial inclusion, inclusive economic growth, and poverty reduction. Results: The implementation of QRIS and digital payment platforms has accelerated MSME transactions. Access to funding through fintech lending has expanded business capital. Strengthening administrative practices, such as basic financial recordkeeping and inventory management, has improved operational efficiency. Research Contributions: This study contributes to increasing MSME income, expanding market reach, and reinforcing their role in supporting the SDGs, particularly in the areas of local economic development and financial inclusion